Are strain genetic effect and heterosis expression altered with culture system and rearing environment in the Portuguese oyster (Crassostrea angulata)?. (22nd November 2016) - In, Vu Van; Sang, Vu Van; O'Connor, Wayne; Van, Phan Thi; Dove, Michael; Knibb, Wayne; Nguyen, Nguyen Hong
Abstract: Re‐ranking of strain additive genetic effect and heterosis expression in different culture environments is not well understood in shellfish species. This study was carried out to estimate the strain additive genetic and heterotic effects on harvest body weight in a 3 × 3 complete diallel cross involving three populations of Portuguese oyster ( Crassostrea angulata ), two populations from Cat Ba (RIA1) and Nam Dinh, northern Vietnam, and an imported stock from China. Strip spawning was applied to produce full‐ and half‐sib families simultaneously of nine cross‐combinations for performance testing at two locations (Cat Ba Island, Hai Phong city and Van Don Island, Quang Ninh province, Vietnam) using two culture systems ('single seed' and 'cultch set'). A total of 7269 individual oysters were examined over a grow‐out period of 270 days. A linear mixed model was used to estimate strain additive genetic and heterotic effects for body weight at harvest. Ranking of strains based on their additive genetic effects did not differ between the locations and culture systems. The non‐additive genetic (heterotic) effects were low and not significantly different from zero for the traits studied among culture systems. There were no significant differences in levels of heterosis for harvest body weight between the two test environments or culture systems. Based on the non‐significant heterotic and large additive genetic effects among strains used for this study, a future breeding programme in this species ( C. angulata ), setting aside issues of diversity, could be based simply on choice among different strains based on their performance.